'A Serious House on Serious Earth': Towards an Understanding of the Church of England's Inheritance of Buildings. Issue 2 (12th April 2018) - Carter, Benjamin
Abstract: The Church of England is blessed with an extraordinary inheritance of church buildings. However, this inheritance, particularly in rural contexts, is increasingly being viewed as a financial millstone and encumbrance to mission. This article takes issue with the largely 'functional' understanding of church buildings which is common place in the Church of England. It will argue that there needs to be a rediscovery of the symbolic and sacramental power of buildings. By reasserting the sacramental and symbolic power of church buildings we can come again to recognize how all church buildings – and not just those blessed with a great history or soaring architecture – exist in part to articulate the ongoing presence and activity of God in creation.